Intervention Effects on Post-Endodontic Pain in Trials Indexed Under Periodontitis: A ClinicalTrials.gov Aggregate-Data Analysis - Annisa Annisa; Aprilia Sari; Kim Sohyuk (Phlox Institute: Indonesian Medical Research Organization, 2025)
Background: Post-endodontic pain is a patient-important outcome, yet posted trial-registry results are difficult to compare because outcome scales, time points, and reporting structures vary. Objective: This study aimed to estimate the magnitude and precision of intervention effects on postoperative pain and to characterize their temporal and multiplicity-adjusted patterns in eligible randomized endodontic trials. Methods: ClinicalTrials.gov records from a frozen query for periodontitis studies with posted results were screened for randomized endodontic trials reporting arm-level pain means, dispersion, and denominators. Official API records were used to verify groups and outcomes. Raw mean differences and Hedges g with 95% confidence intervals were calculated without cross-trial pooling. Standard errors were converted to standard deviations where indicated, independent recruitment cohorts were combined within a trial, and multiplicity was controlled using Holm adjustment. Results: Among 64 records, 11 contained pain-related outcomes and 4 endodontic trials were eligible. The trials enrolled 257 participants; 249 contributed to pain denominators. Nine of 18 non-pooled confidence intervals excluded zero, while 7 comparisons from 2 trials remained significant after Holm adjustment. Photobiomodulation produced lower pain than sham at 0, 6, 12, 24, and 72 hours. Cryotherapy produced lower pain than saline at 24 and 48 hours after adjustment. Estimates for occlusal reduction, GentleWave versus EndoActivator, and ibuprofen/acetaminophen versus ibuprofen were not robustly different. Conclusion: Posted aggregate results revealed treatment- and time-specific signals rather than a common intervention effect. Verified extraction and multiplicity-aware non-pooled analysis improve interpretability, but clinical decisions require full publications and harmonized outcome definitions.